What's the future of business? : changing the way businesses create experiences - Solis, Brian (Wiley, 2013)
Rethink your business model to incorporate the power of ""user"" experiences What's the Future of Business? will galvanize a new movement that aligns the tenets of user experience with the vision of innovative leadership to improve business performance, engagement, and relationships for a new generation of consumerism. It provides an overview of real-world experiences versus ""user"" experiences in relation to products, services, mobile, social media, and commerce, among others. This book explains why experience is everything and how the future of business will come do.